The role of emotional bonding in mediating destination image on tourist loyalty - Lestari, Anik; Noermijanti, Noermijanti; Sumiati, Sumiati; Rofik, Ainur (Technium Business and Management, 2022)
Destination image has become an interesting issue in tourism research, but empirically, the study about destination image relationship and tourist loyalty show diverse result. This study aims to analyse the effect of destination image on loyalty. This study uses quantitative methods. Data collection was carried out using a survey method with questionnaire to tourism visitors. One hundred and ten respondents have been selected as respondent, and path analysis carried out the data analysis.The results showed that the destination’s image affected emotional bonding, and emotional bonding mediated the destination image impact on tourist loyalty.The study was only based on Trenggalek city, East Java Province, Indonesia, and therefore, the results cannot be generalised. The study proves that the emotional bonding variable can replace the role of satisfaction in mediating the effect of destination image on tourist loyalty. The results of this research can be used as a basis for tourism marketers to design marketing strategy to improve consumer intention to revisit the tourism destination. Several studies of the destination image influence on tourist intention to visit have been carried out. However, research that specifically discusses the role of tourist emotional bonding in the influence of destination image on tourist loyalty has not been widely discussed.